Affect the Farthest Star - Cleveland, Harlan (Tufts Archival Research Center, 2006)
Harlan Cleveland describes his beliefs as "ideas that Im willing to do something about" and recounts the satisfaction he derives from helping others achieve basic needs such as justice, security, and a sense of achievement.